Transition‐Metal‐Free Trifluoromethylation of Benzyl Bromides Using Trifluoromethyltrimethylsilane and CsF in 1, 2‐Dimethoxyethane. Issue 5 (18th March 2020) - Nozawa‐Kumada, Kanako; Osawa, Sayuri; Ojima, Takuto; Noguchi, Koto; Shigeno, Masanori; Kondo, Yoshinori
Abstract: An SN 2‐type trifluoromethylation of benzyl halides under transition‐metal‐free conditions has been developed using trifluoromethyltrimethylsilane (CF3 SiMe3, Ruppert−Prakash reagent) and CsF in 1, 2‐dimethoxyethane (DME). Under the developed reaction conditions, the in situ generated trifluoromethyl anion (CF3 − ) overcame the instability and displayed enhanced nucleophilicity in the presence of DME. This method provides an efficient approach for the generation of various (2, 2, 2‐trifluoroethyl)arenes such as those bearing alkyl, alkoxy, halo (F, Cl, and Br) and trifluoromethyl groups on the benzene rings. Abstract : Transition‐metal‐free trifluoromethylation of benzyl halides : A novel (2, 2, 2‐trifluoroethyl)arene synthesis via the SN 2 reaction of benzyl halides using the easy‐to‐handle and stable Ruppert‐Prakash reagent (CF3 SiMe3 ) and CsF in 1, 2‐dimethoxyethane (DME). This reaction proceeds under transition‐metal‐free conditions and can be applied to various benzyl halides.